Ulul Albab Character Formation In Al-Ghazali's Intellectual Tradition: Wahdatul Ulum's Perspective - Sindi Pramitha; Fahrur Rozy; Anggie Sri Utari; Ibnu Alwi Jarkasih Harahap; Zaini Dahlan (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2024)
The term "ulul albab" is frequently mentioned in the Quran. Ulul albab refers to individuals known for their sharp intellect, unclouded by confusion, as well as strong spiritual and intellectual integrity. Drawing on the ideas of Al-Ghazali as a foundation, this study aims to explore Al-Ghazali's thoughts on shaping the character of Ulul Albab from the perspective of Wahdatul Ulum. Through qualitative approaches and a literature review, the integration of reason and revelation, the importance of Sufi practices, and the virtues of ethics in seeking closeness to Allah are analyzed. The research findings demonstrate that Al-Ghazali, as a brilliant Islamic scholar and humanist, mastered various branches of knowledge, ranging from jurisprudence, theology, logic, philosophy, and Sufism and ethics. In Al-Ghazali's view, Ulul Albab are depicted as individuals who combine knowledge and action, possess firm beliefs rooted in true understanding, and develop noble traits reflected in everyday life. This research significantly contributes to enriching insights into the concept of Ulul Albab from the perspective of Al-Ghazali's thought, while highlighting the importance of spiritual and moral practices in attaining perfection as servants of Allah, as well as the integration of reason and revelation.